Acute endurance exercise modulates growth differentiation factor 11 in cerebrospinal fluid of healthy young adults - Schön, Martin; Marček Malenovská, Karin; Nemec, Michal; Alchus Laiferová, Nikoleta; Straka, Igor; Košutzká, Zuzana; Matejička, Peter; Valkovič, Peter; Ukropec, Jozef; Ukropcová, Barbara (Frontiers in Endocrinology, 2023)
Objective: Strong evidence supports the benefits of exercise for healthy ageing, including reduced risk of neurodegenerative diseases. Recent studies suggested interorgan crosstalk as a key element of systemic adaptive response, however, the role of specific molecules in mediating exercise effects on the human brain are not fully understood. In the present study, we explored the exercise-related regulation of Growth Differentiation Factor 11 (GDF11) in cerebrospinal fluid (CSF) and blood. Methods: The samples of serum, plasma and CSF were obtained before and 60min after acute exercise (90min run) from twenty healthy young individuals. Additional serum and plasma samples were collected immediately after run. GDF11 protein content (immunoblotting), body composition (bioelectrical impedance), physical fitness (VO2max, cycle spiroergometry) and cognitive functions (standardized computerized tests, Cogstate) were evaluated. Results: Running decreased GDF11 protein content in CSF (-20.6%. p=0.046), while GDF11 in plasma and serum were not regulated. Two GDF11-specific antibodies of different origin were used to corroborate this result. Individuals with higher physical fitness displayed greater exercise-induced decrease of GDF11 in CSF than those with lower physical fitness (p=0.025). VO2max correlated positively with GDF11 in serum (r=0.63, p=0.020) as well as with the exercise-induced change in GDF11 levels in CSF (r=0.59, p=0.042). Indirect measure of blood-brain barrier permeability (i.e. CSF/serum albumin ratio) tended to positively correlate with CSF/serum GDF11 ratio (p=0.060). CSF levels of GDF11 correlated positively with cognitive functions, including working memory, both before and after run (p<0.05). Conclusion: Running-induced down-regulation of the GDF11 protein in the cerebrospinal fluid of healthy young individuals indicates the potential role of GDF11 in the exercise-induced cross-talk between periphery and the brain.